1975
DOI: 10.1136/pgmj.51.601.790
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of inhaled lead from motor exhaust

Abstract: To assess the contribution of lead in motor exhaust to the total uptake of lead it is necessary to know the amount deposited in the lungs, the uptake thence to blood and other tissues, and the rate of excretion from the body. There (Fig. 1). A similar effect was obtained by drawing the usual chain-aggregate type aerosol through a humidifier.In some experiments the container was exposed to sunlight for about 1 hr so that the aerosol received ultra-violet radiation before inhalation took place. InhalationThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 10 publications
(13 reference statements)
0
9
0
Order By: Relevance
“…Another important factor affecting gastrointestinal absorption is the relative condition of the gut, that is, whether in a fasted or non-fasted state. Radioactive and stable isotope tracer studies have shown that the absence of Ca and other minerals in the gastrointestinal tract at the time of Pb ingestion is a major reason for increased Pb absorption in fasting subjects compared with nonfasting subjects ( Blake and Mann 1983 ; Chamberlain et al 1978 ; Heard and Chamberlain 1982 ; Rabinowitz et al 1976 , 1980 ). When Ca and other minerals are present, however, differences between fasting and nonfasting subjects are not significant ( Heard and Chamberlain 1982 ; Krebs et al 1997 ; Rabinowitz et al 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor affecting gastrointestinal absorption is the relative condition of the gut, that is, whether in a fasted or non-fasted state. Radioactive and stable isotope tracer studies have shown that the absence of Ca and other minerals in the gastrointestinal tract at the time of Pb ingestion is a major reason for increased Pb absorption in fasting subjects compared with nonfasting subjects ( Blake and Mann 1983 ; Chamberlain et al 1978 ; Heard and Chamberlain 1982 ; Rabinowitz et al 1976 , 1980 ). When Ca and other minerals are present, however, differences between fasting and nonfasting subjects are not significant ( Heard and Chamberlain 1982 ; Krebs et al 1997 ; Rabinowitz et al 1980 ).…”
Section: Discussionmentioning
confidence: 99%
“…Animals were exposed to Pb acetate or test material for 15 days, with the dose for each day being administered in two equal portions given at 0900 hr and 1500 hr (2 hr before feeding). We selected these exposure times so that Pb ingestion would occur at a time when the stomach was largely or entirely empty of food, because the presence of food in the stomach is known to reduce Pb absorption (e.g., Blake et al 1983 ; Chamberlain et al 1978 ; Heard and Chamberlain 1982 ; James et al 1985 ; Rabinowitz et al 1980 ).…”
Section: Methodsmentioning
confidence: 99%
“…In these studies, exposures were to particles having mass median aerodynamic diameters below 1 m and, therefore, deposition of the inhaled lead particles can be assumed to have been primarily in the bronchiolar and alveolar regions of the respiratory tract (James et al, 1994 ) where transport of deposited lead to the gastrointestinal tract is likely to have been only a minor component of particle clearance ( Hursh et al, 1969 ). The ICRP lead model includes four deposition compartments from which a total of 95% of deposited lead is absorbed with half -times ranging from 1 h to 2 days, and 5% is transferred to the stomach (Chamberlain et al, 1978 ). The slowest respiratory tract compartment would be expected to have the largest impact on blood lead concentrations resulting from acute inhalation exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Since lead absorbed into the systemic circulation would be expected to have similar biokinetics, regardless of the route of absorption, the concern resides in how well the model simulates deposition and absorption of lead in the respiratory tract. The respiratory tract portion of the ICRP model is empirically based on experimental observations from inhalation studies conducted in adults, which revealed multicompartmental absorption kinetics for deposited lead (Hursh and Mercer, 1970;Hursh et al, 1969;Wells et al, 1975;Chamberlain et al, 1978;Morrow et al, 1980 ). In these studies, exposures were to particles having mass median aerodynamic diameters below 1 m and, therefore, deposition of the inhaled lead particles can be assumed to have been primarily in the bronchiolar and alveolar regions of the respiratory tract (James et al, 1994 ) where transport of deposited lead to the gastrointestinal tract is likely to have been only a minor component of particle clearance ( Hursh et al, 1969 ).…”
Section: Discussionmentioning
confidence: 99%